Answer:
![((x+4)^(2))/(81)+((y-4)^(2))/(4)=1](https://img.qammunity.org/2023/formulas/mathematics/college/9ztx6c2trhjnqh5uz1ztmfootpfl4vqamm.png)
Step-by-step explanation:
The center of the ellipse, (h, k) = (-4, 4)
The length of the major axis = 18
The length of the semi-major axis, a = 18/2 = 9
The length of the minor axis = 4
The length of the semi minor axis, b = 4/2 = 2
The equation of the ellipse is calculated as shown below
![((x-h)^2)/(a^2)+((y-k)^2)/(b^2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/l0626bn68eeug6hf6kdo2ks0r7t63wrkx6.png)
Substitute h = -4, k = 4, a = 9, and b = 2 into the equation
![\begin{gathered} ((x-(-4))^2)/(9^2)+((y-4)^2)/(2^2)=1 \\ \\ ((x+4)^2)/(81)+((y-4)^2)/(4)=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x6go27kdozl54dg131jqm3q5toa11ozoyx.png)
Therefore, the equation of the ellipse is:
![((x+4)^(2))/(81)+((y-4)^(2))/(4)=1](https://img.qammunity.org/2023/formulas/mathematics/college/9ztx6c2trhjnqh5uz1ztmfootpfl4vqamm.png)